Application of “One Syndrome and One Product”nursing mode for inpatients with post-stroke depression (“一证一品”护理模式在中风后抑郁患者护理中的应用) - YANG Yu (杨宇); WANG Xuesong (王雪送); FAN Yan (范艳); LIU Yanna (刘燕娜); HU Shirong (胡世荣) (中西医结合护理)
Objective To explore the application of “One Syndrome and One Product” in care of post-stroke depression. Methods Totally 90 inpatients of post-stroke depression were divided into control (n=45)and observation group (n=45) according on randomized principles. The control group were treated with routine therapy and nursing, while the observation group were treated additionally with the special Traditional Chinese Medicine nursing interventions based on the model of "One Syndrome and One Product". The comparison of depression and self-efficacy between the two groups was conducted before and after the trial. Results After the intervention, the Hamilton Depression Scale(HAMD) score of observation group was lower than that of control group, but the Generalized Self-Efficacy scale (GSES) score of observation group was higher than that of control group, with significant difference(P＜0. 05). Conclusion The special Traditional Chinese Medicine nursing model of “One Syndrome and One Product” can effectively relieve depressive syndrome and improve sense of self-efficacy in residential care of post-stroke depression. (目的 探讨“一证一品”专科特色护理模式在中风后抑郁护理中的应用效果。方法 90例中风后抑郁住院患者随机分为对照组和观察组, 各45例。对照组接受常规治疗和护理, 观察组在对照组基础上开展“一证一品”中医专科特色护理模式。对比2组干预前后抑郁情况、自我效能感。结果 干预后, 观察组汉密顿抑郁量表(HAMD)评分低于对照组, 一般自我效能感量表(GSES)评分高于对照组, 差异有统计学意义(P＜0. 05)。结论 一证一品”中医专科特色护理模式能有效减轻中风后抑郁患者的抑郁情绪, 提高自我效能感。)